2008
DOI: 10.1080/17483100701500173
|View full text |Cite
|
Sign up to set email alerts
|

Indoor wayfinding: Developing a functional interface for individuals with cognitive impairments

Abstract: Our findings suggest that the ability to adapt indoor wayfinding devices for specific users' preferences and needs will be particularly important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 14 publications
0
54
0
1
Order By: Relevance
“…They also more frequently fail to execute a planned wayfinding task than people who do not suffer from dementia. Patients also seem to get confused more easily by conventional navigation aids, like street nameplates [11], not so much because they do not know how to use these but because of problems with understanding language or sight. It was reported often that patients who suffer to dementia make use of salient objects in the surroundings, or 'landmarks', while taking a walk outdoors [1,18].…”
Section: Dementia and Wayfindingmentioning
confidence: 99%
See 1 more Smart Citation
“…They also more frequently fail to execute a planned wayfinding task than people who do not suffer from dementia. Patients also seem to get confused more easily by conventional navigation aids, like street nameplates [11], not so much because they do not know how to use these but because of problems with understanding language or sight. It was reported often that patients who suffer to dementia make use of salient objects in the surroundings, or 'landmarks', while taking a walk outdoors [1,18].…”
Section: Dementia and Wayfindingmentioning
confidence: 99%
“…Alarm systems exist that let the elderly get in touch with a caregiver when they are lost, for example the alarm medallion that with a press on a button can warn the caregiver who then will accompany the person to his or her desired destination. Prototype systems have been tested only for indoor navigation [11]. Andersen et al [2] found that good support for pedestrians with mild dementia can lead to a better quality of life, especially in terms of independence and freedom to move around outdoors.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Maroti et al's [34] sniper localization system uses a handheld as an output device, i.e., to display the sniper's location as computed by the system. Although smart mobile phones are beginning to be able to run limited, GPS/visionanchored augmented reality applications, they generally don't integrate with real-time sensor networks and render mainly cached or web-based data [35]. The Ubicorder's sensor network browsing functionality has directly evolved from the Responsive Environments (ResEnv) Tricorder [11], [36], [37] built earlier by our research team.…”
Section: Browsing Sensor Networkmentioning
confidence: 99%
“…Navigation applications could also make use of the improved location accuracy, again without the need for additional markers as proposed in other navigation systems [20]. Using images of the environment instead of words or maps is more effective for people with cognitive disabilities [1], and would be a pleasant interface for most users. The ubiquity of cellphone usage would not make users requiring assitance stand out.…”
Section: Applicationsmentioning
confidence: 99%
“…In essence, we are trying to provide customized "painted lines on the floor" for users to follow to their destination. Our goal is to overlay directional arrows and navigation instructions onto the image as it is easier to understand directions when they are overlaid directly on the user's own view of his environment, especially for people with cognitive impairments [1]. The inability to get around efficiently can limit integration into the community or affect their ability to be gainfully employed.…”
Section: Introductionmentioning
confidence: 99%